Creating a stable oxide at the surface of black phosphorus - Edmonds, M.; Tadich, A.; Carvalho, A.; Ziletti, A.; O'Donnell, Kane; Koenig, S.; Coker, D.; Özyilmaz, B.; Neto, A.; Fuhrer, M. (American Chemical Society, 2015)
The stability of the surface of in situ cleaved black phosphorus crystals upon exposure to atmosphere is investigated with synchrotron-based photoelectron spectroscopy. After 2 days atmosphere exposure a stable subnanometer layer of primarily P2O5 forms at the surface. The work function increases by 0.1 eV from 3.9 eV for as-cleaved black phosphorus to 4.0 eV after formation of the 0.4 nm thick oxide, with phosphorus core levels shifting by <0.1 eV. The results indicate minimal charge transfer, suggesting that the oxide layer is suitable for passivation or as an interface layer for further dielectric deposition.